ENHANCING THE EFFICIENCY OF SCIENTIFIC RESEARCH IN HIGHER EDUCATION SYSTEMS (European Journal of Economics, Finance and Business Development, 2025)
This study examines mechanisms to enhance the efficiency of scientific research within higher education systems. Focusing on the integration of advanced technologies, international collaboration, and the development of research infrastructure, the research analyzes current challenges and proposes strategic solutions. Findings suggest that adopting innovative approaches and fostering global partnerships are critical for improving research outcomes in higher education institutions.